(untitled) (Citizenship in Action: Extension and Culture Magazine, 2023)
The use of technologies is a propitious way to insert and involve the student in digital reading and writing practices. Therefore, this report brings part of the actions of the extension project "Between legends and tales: the role of new technologies in the process of Literacy" with the objective of contributing to the process of digital literacy and reading-writing with Amazonian legends of 3rd grade students from public schools in Belém-PA. Two workshops are reported here, held in August and November 2018, with 3rd grade students from two public schools and under the leadership of graduates participating in the project. The first workshop had students from schools A and B, and the second, only students from school A. In workshop 1, students from the schools involved (A and B) participated in the telling of the legend of Curupira. In the sequence, they were guided to retell the legend in the form of comics, through the software "HagáQuê", producing the retextualization; this dynamic was repeated in workshop 2, in school A, with the legend of Boto. In the first workshop, a certain dexterity of the students was noticed regarding the use of the application, but with limitations in conventional writing, in the selection and combination of letters to type words and phrases, it isonly more evident in non-alphabetic students, although they all showed the interest in reading and writing or typing, attracted by the technological novelty. In the second workshop, held as a complement at school A, advances in digital handling and better writing performance were observed, compared to the moment of the workshop1, through the Hagáquê software. It was concluded that the use of digital technologies, as tools for literacy and literacy of students with difficulties in reading and writing, proved to be a timely strategy to face this challenging reality, as well as training the teacher who needs to know and know how to deal with these challenges, in favor of a digital literacy linked to the acquisition process of reading and writing in a social context. Keywords: Literacy. Technologies. Digital literacy. Reading. Writing